Relativity visualized - Epstein, Lewis C. (San Francisco : Insight Press, 2000)
Explains Albert Einstein's theories of relativity through diagrams, illstrations, and simplified language.
Includes index.
Adult
Keywords: Physics -- Philosophy; Relativity (Physics); Physics -- Philosophy; Relativity (Physics)